2009
DOI: 10.1038/emboj.2009.60
|View full text |Cite
|
Sign up to set email alerts
|

The MRX complex stabilizes the replisome independently of the S phase checkpoint during replication stress

Abstract: The Mre11-Rad50-Xrs2 (MRX) complex has an important function in the maintenance of genomic integrity by contributing to the detection and repair of chromosome breaks. Here we show that the complex is recruited to sites of paused forks where it stabilizes the association of essential replisome components. Interestingly, this function is not dependent on the S phase checkpoint or the nuclease activity of Mre11. We find that disruption of the MRX complex leads to a loss of fork recovery and a failure to properly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
84
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(91 citation statements)
references
References 75 publications
7
84
0
Order By: Relevance
“…The lesser increase of fragility in the mre11D rad52D CAG-70 strain compared to the mre11D single mutant could either be because of noise in the assay or a decreased efficiency of BIR at this repeat due to unprocessed hairpin-capped ends (see below). In addition, presence of the Mre11 protein is likely important for preventing collapse of forks stalled or reversed at the CAG repeat tract (Kerrest et al 2009), as Mre11 has been shown to prevent accumulation of DSB ends during replication and promote replication fork restart in Xenopus extracts (Costanzo et al 2001;Trenz et al 2006), and it locates to and stabilizes replisomes stalled by hydroxyurea treatment in yeast (Tittel-Elmer et al 2009). Thus, the large increase in fragility in the mre11D strain is likely a reflection of roles both in preventing fork collapse and in repairing breaks that have occurred by other means.…”
Section: Discussionmentioning
confidence: 99%
“…The lesser increase of fragility in the mre11D rad52D CAG-70 strain compared to the mre11D single mutant could either be because of noise in the assay or a decreased efficiency of BIR at this repeat due to unprocessed hairpin-capped ends (see below). In addition, presence of the Mre11 protein is likely important for preventing collapse of forks stalled or reversed at the CAG repeat tract (Kerrest et al 2009), as Mre11 has been shown to prevent accumulation of DSB ends during replication and promote replication fork restart in Xenopus extracts (Costanzo et al 2001;Trenz et al 2006), and it locates to and stabilizes replisomes stalled by hydroxyurea treatment in yeast (Tittel-Elmer et al 2009). Thus, the large increase in fragility in the mre11D strain is likely a reflection of roles both in preventing fork collapse and in repairing breaks that have occurred by other means.…”
Section: Discussionmentioning
confidence: 99%
“…Chromatin Immunoprecipitation-ChIP/quantitative realtime PCR (qPCR) was performed as described previously (32)(33)(34). DNA quantification by real-time PCR was performed on an ABI 7900 sequence detector system at the Southern Alberta Cancer Research Institute.…”
Section: Methodsmentioning
confidence: 99%
“…One measure of replication correctness during replication stress is to monitor replisome association with stalled forks by ChIP. The recovered DNA from the ChIP was quantified by qPCR with primer pairs to two early-firing origins, ARS305 and ARS607, with late-firing ARS501 serving as a negative control (32)(33)(34). We determined the association of DNA polymerase ⑀ by monitoring Myc-Pol2 recovery with stalled forks when cells were released into S phase in the presence of HU at the indicated time points.…”
Section: Nse5 Interacts With Sumo and Is Required For Smc5mentioning
confidence: 99%
“…However, the MRN nuclease activity is not required for slowing in response to DNA damage in fission yeast (de Jager et al 2001;Limbo et al 2007;Porter-Goff and Rhind 2009). Therefore, we speculate that MRN alters Rhp51-mediated recombination through its DNA-binding activity at forks, possibly by bridging of the two nascent sister chromatids during replication (de Jager et al 2001;Tittel-Elmer et al 2009). …”
Section: Mrn Mutants Display Partial Defects In Slowingmentioning
confidence: 99%